2010
DOI: 10.1103/physrevb.81.155301
|View full text |Cite
|
Sign up to set email alerts
|

Continuously tunable band gap in GaN/AlN (0001) superlattices via built-in electric field

Abstract: Based on all-electron density-functional theory calculations using the generalized gradient approximation, we demonstrate the continuous tunability of the band gap and strength of the built-in electric field in GaN/AlN ͑0001͒ superlattices by control of the thickness of both the well ͑GaN͒ and barrier ͑AlN͒ regions. The effects of strain for these quantities are also studied. Calculations taking into account the self-interaction correction exhibit the same dependence on thickness. The calculated electric field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…In addition, comparing the values for SLs that have a different number of InN and AlN layers but which have the same In composition in total (e.g., values at x = 0.5), we found that the bandgaps decreased with an increase in the number of SL layers. This tendency can be explained in connection with the built‐in electric field . The quantum‐confined Stark effect increases with the number of AlN layers resulting in decreasing bandgap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, comparing the values for SLs that have a different number of InN and AlN layers but which have the same In composition in total (e.g., values at x = 0.5), we found that the bandgaps decreased with an increase in the number of SL layers. This tendency can be explained in connection with the built‐in electric field . The quantum‐confined Stark effect increases with the number of AlN layers resulting in decreasing bandgap.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable efforts have already been made for understanding the electronic band structure of III–V nitride alloys (InGaN, AlGaN, and AlInN) and SLs (InN/GaN and GaN/AlN) . However, there are few reports in the open literature on the bandgap and on the synthesis of InN/AlN SLs.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that the latter factor tends to decrease the bandgap. Overall, the shellthickness dependence of the bandgap in graphene/graphane QDs is much weaker than that of III-Nitride quantum well structures, 18,19 and also of that for GQDs embedded in hexagonal BN, 20 indicating a strong confinement even using rather thin shells.…”
mentioning
confidence: 90%
“…DFT calculations were used to polar AlN/GaN heterostructures, 31 PHYSICS 113, 193706 (2013) comparable magnitude to the built-in contribution. 33,34 Since the electric field was determined using a change of the 1 s N state energy, the resolution was less than 1 double atomic layer, which does not provide a precise insight into the physics of the MQWs system.…”
Section: Introductionmentioning
confidence: 99%